A systematic review of HIV/AIDS-related stigma and discrimination in India: Current understanding and future needs - Shalini Bharat (SAHARA-J, 2011)
HIV/AIDS-related stigma is recognised as a major barrier to HIV prevention efforts and an impediment to mitigating its impact on individuals and communities. This paper reviews the existing research literature on AIDS stigma in India with the objective of documenting the current status of research, highlighting major findings and identifying key gaps remaining. Thirty publications were identified through a careful search of which a majority focused on stigma assessment and very few on stigma measurement, conceptual aspects of stigma or stigma reduction interventions. A few standardised stigma measures are available but more are required to assess causes of stigma among general population and compounded and internalised stigma among positive people. Research exploring linkages between stigma and HIV services uptake or the effect of HIV care and treatment programs on stigma levels are largely missing and need to be prioritised. In addition, more research is needed to advance conceptual understanding of stigma within the cultural context of the country including research on the neglected groups such as, transgender people. Context-specific (health care, community) interventions are needed to address various forms of stigma – enacted, perceived, internalised and layered – including structural approaches besides inter-personal and information-based approaches. A major gap relates to meager research on developing and evaluating stigma reduction interventions and needs priority focus. Overall, the review recommends developing a national agenda on AIDS stigma research and interventions to help realise the government's goal of stigma reduction.